2007
DOI: 10.1016/j.actbio.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics and biophysics of cancer cells☆

Abstract: The past decade has seen substantial growth in research into how changes in the biomechanical and biophysical properties of cells and subcellular structures influence, and are influenced by, the onset and progression of human diseases. This paper presents an overview of the rapidly expanding, nascent field of research that deals with the biomechanics and biophysics of cancer cells. The review begins with some key observations on the biology of cancer cells and on the role of actin microfilaments, intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
735
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,029 publications
(753 citation statements)
references
References 148 publications
(237 reference statements)
14
735
1
3
Order By: Relevance
“…Previously, it has been shown that mechanical force delivered by the AFM tip can induce various chemo-mechanical responses [167][168][169]. In recent work, it has also been shown that the mechanical environment of many cell types (including cancer and stem cells) can be used to control and alter gene expression and differentiation pathways [21-25, 164,170,171]. We now have the tools to measure mechanical properties, and we have the tools to alter the mechanical environment of a cell or even deliver well-defined forces to a cell.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been shown that mechanical force delivered by the AFM tip can induce various chemo-mechanical responses [167][168][169]. In recent work, it has also been shown that the mechanical environment of many cell types (including cancer and stem cells) can be used to control and alter gene expression and differentiation pathways [21-25, 164,170,171]. We now have the tools to measure mechanical properties, and we have the tools to alter the mechanical environment of a cell or even deliver well-defined forces to a cell.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The unique biochemical and biophysical properties enable a cell to fulfill its specific functions and adapt to its surrounding environment. Physiological changes within the cells are accompanied by chemical and physical modifications and reorganization.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of clinical relevance is due to the very low measurement throughput and tedious operation procedures of conventional techniques for measuring the biophysical properties of cells. 4,[7][8][9] Compared to conventional techniques, the advantages of small sample volume, integration capability, biocompatibility and fast response make microfluidic technologies attractive for studying cells. Recent decades have witnessed significant advances of microfluidic technologies for biochemical characterization of cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Once oxidative damage occurs in proteins, their corresponding functions reduce or disappear, thereby inducing aging, diabetes, cancer, cardiovascular disease, and other pathological conditions. [5][6][7] The inherent correlations between the aforementioned diseases and protein oxidative damage have been widely confirmed and have aroused wide attention. 1,[8][9][10] Investigation into the oxidative damage mechanism of proteins not only benefits to clarify protein functions, but also contributes to disease diagnosis, prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%